No robust evidence for an interaction between early-life adversity and protective factors on global and regional brain volumes - Cortés Hidalgo, Andrea; Tiemeier, Henning; Metcalf, Stephen A.; Monninger, Maximilian; Meyer-Lindenberg, Andreas; Aggensteiner, Pascal-M.; Bakermans‑Kranenburg, Marian J.; White, Tonya; Banaschewski, Tobias; van IJzendoorn, Marinus H.; Holz, Nathalie E. (Developmental cognitive neuroscience, 2022)
Childhood adversity is associated with brain morphology and poor psychological outcomes, and evidence of protective factors counteracting childhood adversity effects on neurobiology is scarce. We examined the interplay of childhood adversity with protective factors in relation to brain morphology in two independent longitudinal cohorts, the Generation R Study (N = 3008) and the Mannheim Study of Children at Risk (MARS) (N = 179). Cumulative exposure to 12 adverse events was assessed across childhood until age 9 years in Generation R and 11 years in MARS. Protective factors (temperament, cognition, self-esteem, maternal sensitivity, friendship quality) were assessed at various time-points during childhood. Global brain volumes and volumes of amygdala, hippocampus, and the anterior cingulate, medial orbitofrontal and rostral middle frontal cortices were assessed with anatomical scans at 10 years in Generation R and at 25 years in MARS. Childhood adversity was related to smaller cortical grey matter, cerebral white matter, and cerebellar volumes in children. Also, no buffering effects of protective factors on the association between adversity and the brain outcomes survived multiple testing correction. We found no robust evidence for an interaction between protective factors and childhood adversity on broad brain structural measures. Small interaction effects observed in one cohort only warrant further investigation.